DEFICIT COMMUNICATIONNEL DANS LA LUTTE CONTRE LE PALUDISME DANS LA ZONE DE SANTE RURALE DE YALEKO. - ASAKA John, ANGONDO; Christophe ATWAIWANI LIKONO; Prosper IDJUMBE WOLA (IJRDO - Journal of Social Science and Humanities Research, 2019)
The deficit communicationnel in Africa in general and in RDC is in particular a living and incontestable reality. He/it existed before the meeting of the civilizations and continuous again his/her/its fellow of path especially in the farming surroundings where he/it is consumed more. Several reasons contribute to the use of this communication showing a deficit notably the precipitation, the economy of the time, the hope to have the customers (patient) shortly, the slander, the hold of power on the customer (patient), the démotivation of the actors, the message of sensitization too technique, the absence of the public sensitization meetings on the malaria, etc. The present survey pursues the objectives below: to determine the level of cover of information on the malaria in the community and to identify the possible consequences of the deficit communicationnel of the struggle against the malaria on the health of the individuals. These reasons are considered as the deepest reasons of the deficit communicationnel that generate more the negative consequences than positive. It is why, the deficit communicationnel in the struggle against the malaria is consumed badly as such, it constitutes one of the factors of the resurgence of the infectious illnesses of the underdevelopment springs that deserves a particular attention because without a good health, all effort of the development is vowed to the failure.